REVESZ SYNDROME AND DIFFERENTIAL DIAGNOSIS OF PANCYTOPENIA AND APLASTIC ANEMIA - CASE REPORT - Matjaž Homšak; Mario Kulaš; Tomaž Prelog; Simona Lucija Avčin; Tina Vipotnik Vesnaver (The Society for Children with Metabolic Disorders, 2023)
We are presenting a case of a boy with Revesz syndrome, and through an example of his diagnostic pathway, we are presenting a differential diagnosis of pancytopenia and aplastic anaemia. Revesz syndrome is a rare and severe form of dyskeratosis congenita, belonging to the short telomere syndromes group. In addition to changes of skin and mucous membranes and aplastic anaemia, which are typical for dyskeratosis congenita, Revesz syndrome is carcinoma predisposing syndrome, characterised by microcephaly, calcifications in the brain, intrauterine growth restriction, and exudative retinopathy. We also presented a differential diagnosis of pancytopenia and aplastic anaemia through the boy's diagnostic pathway.